Timeline of cognitive impairments after radiotherapy for head and neck cancer: A review - K. Wickborn; C.W.J. van der Weijden; E.F.J. de Vries; T.W.H. Meijer; M.C.A. Kramer; J.M. Spikman; A.M. Buunk; A. van der Hoorn (Clinical and Translational Radiation Oncology)
Background: With advances in cancer treatments, long-term impairments of survivors have become more apparent. Radiotherapy of tumors in or near the brain can potentially induce cognitive impairments, impacting the quality of life of survivors. Currently, there is a lack of comprehensive information on the timeline of cognitive impairments following radiotherapy for head and neck cancer (HNC). To address this gap, we conducted a literature review on cognitive impairments observed after radiotherapy for HNC. Methods: The literature review was conducted using PubMed, Web of Science, PsycINFO, and Google Scholar. Search terms included the following keywords: head and neck tumors, radiotherapy, treatment responses, cognitive impairments, as well as variants and related subcategories. Result: Our review encompassed 23 studies involving a total of 1059 HNC patients, predominantly nasopharyngeal carcinoma. Overall, studies indicated a decline in cognitive performance post-radiotherapy compared to baseline scores, control groups, or normative data. The literature on acute effects is scarce and studies with complete neuropsychological assessments are missing. Cognitive impairments were prevalent in the majority of patients at six to 12 months post-radiotherapy, with memory deficits being the most prominent. Long-term assessments demonstrated that these cognitive deficits persisted even beyond seven years, suggesting a potentially irreversible decline in cognition following radiotherapy. Conclusion: Cognitive impairments are frequently observed at least six months after radiotherapy. Standardized cognitive assessments are imperative to evaluate impairments in individual patients. Future research in HNC should integrate neuropsychological evaluations to enhance our understanding of domain-specific impairments and the complete timeline of cognitive changes after radiotherapy.